Analisis Perbandingan Kinerja Reksa Dana Saham Syariah dan Reksa Dana Konvensional pada Periode Krisis dan Periode Sesudah Krisis Subprime Mortgage - , Arif Rahman, Prof. Dr. Tandelilin Eduardus, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In recent decades, investing in mutual funds is a phenomenon that many investors done, because they think this type of investment can provide an optimal return with minimal risk. In the current investment growth climate in Indonesia, at the end of 2007 the financial market in Indonesia turmoil as effect of the U.S. subprime mortgage crisis. The objective this study are